Evaluation of Parking Characteristics and Parking Demand with PTV Vissim 8.0 at Rejowinangun Market, Magelang: Evaluasi Karakteristik dan Kebutuhan Parkir Menggunakan PTV Vissim 8.0 di Pasar Rejowinangun Magelang - Soebari, Hashifah Putri; Woro Partini Maryunani; Lalu Samsul Aswadi (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
Rejowinangun Market is  traditional market in Magelang City.  Volume of vehicles in the parking area is also expected to increase. Therefore, this study aims to evaluate the characteristics, layout arrangement, and parking needs in the Rejowinangun market to better understand the current situation in the parking area. Research was conducted using the cordon survey method and direct observation at 06.00-08.00 and 12.00-14.00 on three days.  The results indicate that the highest occupation of the parking area occurred of 1,468 motorcycles and 40 cars parked during the observation period. The number of parked vehicles at 489 motorcycles and 23 cars. The parking turnover rate at 3.231 and 3.778 for motorcycles and cars. Importantly, the parking index that the current parking area is overloaded with cars (index value of 115%), which is not the case for motorcycles (index value of 46%). Parking model with PTV Vissim shows the highest occupancy on the second floor, with values of 54.63% and 52.35% for motorcycles and cars. The highest level of parking block space (0.04%) was found in the motorcycle parking area on the second floor. The validity further shows that the parking model is valid and therefore the results of this study are reliable.